Oyster Aquaculture Site Selection Using High-Resolution Remote Sensing: A Case Study in the Gulf of Maine, United States - Jiang, Binbin; Boss, Emmanuel; Kiffney, Thomas; Hesketh, Gabriel; Bourdin, Guillaume; Fan, Daidu; Brady, Damian C. (Frontiers in Marine Science, 2022)
Aquaculture of the eastern oyster, Crassostrea virginica, is an expanding industry in the US, particularly in, the Gulf of Maine. High resolution ocean color satellites launched in the last decade potentially provide aquaculture relevant water-quality parameters. However, remote sensing products, such as temperature, Suspended Particulate Matter (SPM), and Chlorophyll a (Chl a), are not produced operationally and interested users need to derive them on their own. Deriving water quality parameters first requires the application of an atmospheric correction and then application of an algorithm to estimate the target parameter. Here, we use five correction schemes and two algorithms to derive SPM and Chl a from the Sentinel 2A&B satellites Multispectral Instrument color sensor data. The most consistent local approach is chosen by comparing remote sensing parameters with in situ observations from buoys. Then, we used the derived Chl a, SPM, and SST (the latter from Landsat-8) to estimate an Oyster Suitability Index (OSI) along transects in five estuaries in the Gulf of Maine. High OSI values are consistent with current locations of high density aquaculture development and suggest new places where oyster aquaculture is likely to be successful.